2020
DOI: 10.3390/ijerph17072347
|View full text |Cite
|
Sign up to set email alerts
|

Getting Old Well in Sub Saharan Africa: Exploring the Social and Structural Drivers of Subjective Wellbeing among Elderly Men and Women in Uganda

Abstract: While literature attempts to explain why self-reported subjective wellbeing (SWB) generally increases with age in most high-income countries based on a social determinants of a health framework, little work attempts to explain the low levels of self-report SWB among older persons in sub-Saharan Africa. Using the 2013 Uganda Study on Global Aging and Health with 470 individuals, this research examines (i) direct and indirect effects of age on SWB through social and structural determinants, and (ii) how direct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…The dominating global meaning-system for all but one participant seemed to be a fusion of Christian and traditional African worldviews. In our study, remarkable differences were noticed between the conditions of men and women as women were reported to suffer harsher conditions affecting their functional ability and meaning-making, which is in line with the findings of, for example, Rishworth et al ( 2020 ). The respondents in this study are trapped in chronic poverty that embraces intergenerational and durational dimensions, where especially widowed, disabled, women, and those living alone are prone to chronic poverty Najjumba-Mulindwa ( 2003 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The dominating global meaning-system for all but one participant seemed to be a fusion of Christian and traditional African worldviews. In our study, remarkable differences were noticed between the conditions of men and women as women were reported to suffer harsher conditions affecting their functional ability and meaning-making, which is in line with the findings of, for example, Rishworth et al ( 2020 ). The respondents in this study are trapped in chronic poverty that embraces intergenerational and durational dimensions, where especially widowed, disabled, women, and those living alone are prone to chronic poverty Najjumba-Mulindwa ( 2003 ).…”
Section: Discussionsupporting
confidence: 92%
“…Women, consequently, suffer accumulated disadvantages and in a study by Rishworth et al ( 2020 ), lower subjectively reported wellbeing was found among older women than men in Uganda. This is no surprise given that meaning and wellbeing are strongly related, but dependent on the context:…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As for the pension, women might have put more value on social contacts than on financial resources, as previously stated. Financial assets were more strongly related to men’s subjective well-being than women [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%